The Process of Making Tempe Benguk as Tourist Attraction in Kulon Progo Yogyakarta - Sari, Dhanik Puspita (E-Journal of Tourism; Volume 4 Number 2 (September 2017)DO - 10.24922/eot.v4i2.36399, 2017)
This research discuss the process of making tempe with benguk bean  (Mucuna pruriens)  as the raw material that can be developed into a form of cultural tourism attractions which aims to improve the income level of the local community in the area of Kulon Progo Regency, Yogyakarta. The used of Benguk Bean based on its originally that only can be found around this region and cannot be treated carelessly due to contain toxic compounds which must be removed. The process and method of cooking is still done in traditional ways, it begin by washing the benguk bean, boiling to fermenting and transform into edible food. The makers still using the traditional stove with firewood or old coconut leaf, bamboo strainer, using ashes, yeast, and banana leaves or teak leaves. This study uses a qualitative study approach. The data used are primary and secondary data collected in several ways including observation, in-depth interviews, documentation and litelature study. This study will focus on the activities done in the process of making tempe benguk as a tourist attraction using Mix activties: the nature of activities in tourism destination.